On the Merkulov construction of A_ ∞ -(co)algebras - Herscovich, E. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 512.5 The aim of this short note is to complete some aspects of a theorem proved by S. Merkulov in [Int. Math. Res. Not. IMRN. – 1999. – 3. – P. 153 – 167] (Theorem 3.4), as well as to provide a complete proof of the dual result for dg coalgebras.